Формування системи менеджменту якості навчальної організації - Влащенко, Л. Г.; Грищенко, Т. Б.; Нікітенко, О. М. (ДонНУЕТ, 2007)
Формування системи менеджменту якості навчальної організації
Keywords: якість освіти; бібліотека